Measuring Traffic Flow using Video Cameras - Mutharpavalar, Ashaashvini (2018)
Developing an Intelligent Transportation System (ITS) that contains the basic information of the real-time traffic flow helps Lembaga Lebuhraya Malaysia to monitor and manage the traffic flow of our country. The main purpose of this paper is to detect and count vehicles along with their direction in real-time traffic flow by using multiple IP-based cameras. Identifying the best image processing techniques for vehicle detections and developing a complete transportation system for vehicle counting using the live videos from multiple IP-based camera has been the scope of study of this paper. Open Source Computer Vision Library (OpenCV) is used to develop the ITS as OpenCV was designed for computational efficiency and with a strong focus on real-time application. Python programming language is used as OpenCV has Python interfaces.